2022
DOI: 10.3389/fphar.2022.918493
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Pharmacogenomics-Guided Prescribing to Prevent Gene-Drug-Related Deaths: A Decision-Analytic Model

Abstract: Aim: Prospective studies support the clinical impact of pharmacogenomics (PGx)-guided prescribing to reduce severe and potentially fatal adverse effects. Drug-gene interactions (DGIs) preventing potential drug-related deaths have been categorized as “essential” by the Dutch Pharmacogenetics Working Group (DPWG). The collective clinical impact and cost-effectiveness of this sub-set is yet undetermined. Therefore, we aim to assess impact and cost-effectiveness of “essential” PGx tests for prevention of gene-drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 49 publications
(69 reference statements)
0
12
0
Order By: Relevance
“…Overall, the benefits and cost-effectiveness of implementing DPYD genotyping prior to FP dosing have been shown in several prospective trials and meta-analyses ( Meulendijks et al, 2015 ; Henricks et al, 2018 ; Brooks et al, 2022 ; Glewis et al, 2022 ; van der Wouden et al, 2022 ). Regulatory agencies such as the Food and Drug Administration (FDA) and European Medicine Agency (EMA), have moved towards recognizing the importance of the application of DPYD genotyping in clinical practice.…”
Section: Fluoropyrimidine Pharmacogenomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the benefits and cost-effectiveness of implementing DPYD genotyping prior to FP dosing have been shown in several prospective trials and meta-analyses ( Meulendijks et al, 2015 ; Henricks et al, 2018 ; Brooks et al, 2022 ; Glewis et al, 2022 ; van der Wouden et al, 2022 ). Regulatory agencies such as the Food and Drug Administration (FDA) and European Medicine Agency (EMA), have moved towards recognizing the importance of the application of DPYD genotyping in clinical practice.…”
Section: Fluoropyrimidine Pharmacogenomicsmentioning
confidence: 99%
“…Pre-existing diseases, such as cardiovascular diseases (CVD), hepatic impairment, and renal insufficiency, as well as CVD risk factors (hypertension, hyperlipidemia and smoking), have been studied as for their association with increased risk for 5-FU-induced cardiotoxicity (Brutcher et al, 2018;Sara et al, 2018). The perception of incorporating non-genetic factors into polygenic risk score models is currently being evaluated for disease risk assessment (van Dam et al, 2023). This approach holds promise to increase the discriminative power of the often low variance explained solely by the genetic factors for the predictive outcome(s).…”
Section: A Polygenic Algorithm For Fp Dosing: New Challenges In Oncologymentioning
confidence: 99%
“…In addition, an interesting study reviewed 44 economic evaluations that investigated the cost-effectiveness of pharmacogenetic strategy. The study concluded that pharmacogenetic strategy produced both improved health outcomes and cost savings (van der Wouden et al, 2022).…”
Section: Genetic Human Evaluation Might Improve Studies In Pharmacoec...mentioning
confidence: 99%
“…Main examples of Pharmacogenomics emerged from clinical observation in differences on drug responses to standardized drugs dose and from observation on plasmatic and urinary concentration of the drug or its metabolites (W. Zhao & Meng, 2022). In this context, pharmacogenomics can help selecting the most appropriate pharmacological agent for a given patient and help the development of cost-effective treatments (Ross et al, 2012;van der Wouden, Marck, Guchelaar, Swen, & van den Hout, 2022). In this review we will approach the therapeutic implications of genetic differences and the Pharmacogenomics potential to improve drug treatments and its application in pharmaceutical industry.…”
Section: Introductionmentioning
confidence: 99%
“…National Institute of General Medical Sciences, 2023 ). The incorporation of PGx information into the clinical care of patients aims to maximize therapeutic efficacy while minimizing adverse events and toxicities, thereby, improving patient outcomes and decreasing healthcare costs ( Jarvis et al, 2022 ; Morris et al, 2022 ; van der Wouden et al, 2022 ). The benefits of PGx guided therapy have been shown in multiple clinical settings ( Mega et al, 2010 ; Cavallari et al, 2018 ; Greden et al, 2019 ; Pereira et al, 2020 ; Oslin et al, 2022 ; Swen et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%